First report of SYNE1 arthrogryposis multiplex congenita from Saudi Arabia with a novel mutation: a case report - Naglaa M. Kamal; AlaaEddin M. Alzeky; Maher R. Omair; Ruwayd A. Attar; Abdullah M. Alotaibi; Abdullah Safar; Nawal S. Alosaimi; Sara A. S. Abosabie (BMC, 2022)
Abstract Background Myogenic Arthrogryposis Multiplex Congenita type 3 (AMC-3), is a rare congenital condition characterized by severe hypotonia, club feet, and multiple joint contractures often affecting both arms and legs which start prior to birth. Case presentation We report a full-term neonate born to first-degree cousins from fourth-generation consanguineous families, who had with antenatal history of reduced fetal movements. At birth, he was noticed to have bilateral club feet, arthrogryposis, severe hypotonia, and absent deep tendon reflexes. The patient developed difficulty in breathing probably attributed to his generalized severe hypotonia, necessitating mechanical ventilation. His creatinine-phospho-kinase, electromyogram, and brain magnetic resonance imaging were normal. Whole-exome sequencing (WES) was requested for the genetic diagnosis of the case. WES identified a novel homozygous variant c.23415-3799C > G p. in the synaptic nuclear envelope protein1 [SYNE1] gene. Seven out of 20 bioinformatic in silico programs predicted a pathogenic effect for this variant. Segregation analysis of the variant in the parents and siblings revealed that both parents and one sibling were heterozygous for the same mutation which proved the variant significance and its autosomal recessive pattern of inheritance. Conclusions AMC3 should be suspected in patients with decreased fetal movements, severe hypotonia, absent deep tendon reflexes, and arthrogryposis. SYNE1 gene mutations can be the underlying genetic defect and molecular genetic testing can prove the diagnosis.